The Growing Epidemic of Diabetes Mellitus - Lovic, Dragan; Piperidou, Alexia; Zografou, Ioanna; Grassos, Haralambos; Pittaras, Andreas; Manolis, Athanasios (Current Vascular Pharmacology, 2020)
Background: During the past decades, the prevalence of diabetes (DM) has increased significantly, mainly as a result of continuous rise in the incidence of type 2 DM. According to World Health Organization statistics, >422 million adults globally were suffering from DM in 2014 and a continuous rise in DM prevalence is expected. Objective: The present review considers recent epidemiological data providing worldwide estimates regarding the incidence of DM. Methods: A comprehensive literature search was conducted to identify available data from epidemiological studies evaluating the current burden of DM. Results: Over the past few decades the prevalence of DM has risen significantly in nearly all countries and may be considered as a growing epidemic. Urbanization and income status are major factors which influence current rates in the prevalence studies introducing interesting differences between several population groups. Conclusion: Having recognized the global burden of DM, we now realize the urgent need for effective interventions. In order to monitor the public-health strategies and design effective future interventions we need reliable global estimates regarding the prevalence of DM.
Keywords: type 1 diabetes